(untitled) (Baghdad Science Journal, 2023)
The game theory has been applied to all situations where agents’ (people or companies) actions are utility-maximizing, and the collaborative offshoot of game theory has proven to be a robust tool for creating effective collaboration strategies in a broad range of applications. In this paper first, we employ the Banzhaf values to show the potential cost to waste producers in the case of a cooperation and to reduce the overall costs of processing non-recyclable waste during cooperation between producers. Secondly, we propose an application of the methodology to study a case for five waste producers’ waste management in the Al-Mahmudiya factory with the aim of displaying the potential cost to waste producers in case of cooperation. Lastly, the obtained results of the proposed framework will strongly help professionals to formulate and improve well-organized strategies for the waste management system of the future.